Pola Komunikasi Tutor dengan Anak Jalanan di Sekolah Alternatif Anak Jalanan (SAAJA) Jakarta Selatan - Safitri, Annisa Putri; Sari, Wina Puspita; Putriana, Muria (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
In the context of Street Children Schools, communication is not only between parents and children but also involves interactions between children and tutors. This study aims to identify the communication patterns used by tutors with street children at the Alternative Street Children School (SAAJA) and the challenges encountered. Using a qualitative approach and descriptive method, data were collected through interviews and observations. Purposive sampling was employed to select informants, focusing on the Alternative Street Children School Foundation, Tutors Mrs. Nunung and Mrs. Iin, and the street children of SAAJA. Both primary and secondary data sources were utilized. Data analysis followed three stages: data reduction, data presentation, and conclusion drawing. Validity was ensured through source and technique triangulation. The study found that the wheel and star communication patterns are used by tutors at SAAJA, proving effective in the teaching process through two-way communication. Challenges faced by SAAJA include issues with teaching staff and the students' external environment. Overall, the study concludes that there is positive feedback and effective daily communication between tutors and street children during the learning process, with well-established communication patterns.